Looking closely at what they say and what it tells us: Experiences in a digital learning space - Khoza, L. M.; van der Merwe, K. (South African Journal of Higher Education, 2022)
This study explores lecturer and student experiences of using the Learning Management System (LMS) within a Faculty at a South African University. The results of the study highlight the extent to which lecturers and students engage with the LMS. This article aims to determine the following: 1) the value that lecturers and students place on using the LMS as a platform to facilitate learning and teaching, 2) the typical resources, activities and assessments that lecturers and students place value on and why, and 3) to compare lecturer and student perspectives on the best utilization of the LMS. Quantitative data were collected from the LMS and qualitative data collected from lecturers and undergraduate students through questionnaires and focus groups. A Social Constructivist framework was adopted as a lens for analysis of collected data. The results show resources are valued the most by both lecturers and students but the majority of students only access, on average, just more than half of the postings. In terms of the constructs of the Social Constructivist framework, Learning and Connectedness showed positive responses, while improvement is necessary for Making Meaning and Agency.